2007
DOI: 10.1158/0008-5472.can-06-3332
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic Androgens and Androgen-Regulated Gene Expression Persist after Testosterone Suppression: Therapeutic Implications for Castration-Resistant Prostate Cancer

Abstract: Androgen deprivation therapy (ADT) remains the primary treatment for advanced prostate cancer. The efficacy of ADT has not been rigorously evaluated by demonstrating suppression of prostatic androgen activity at the target tissue and molecular level. We determined the efficacy and consistency of medical castration in suppressing prostatic androgen levels and androgen-regulated gene expression. Androgen levels and androgen-regulated gene expression (by microarray profiling, quantitative reverse transcription-PC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
288
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(309 citation statements)
references
References 43 publications
15
288
1
5
Order By: Relevance
“…However, standard androgen deprivation did not consistently suppress androgen-dependent gene expression. Many androgen-responsive genes were not suppressed even after 9 months of neoadjuvant androgen deprivation therapy [30]. Androgenindependent prostate cancer may be the consequence of molecular events that are mediated by abnormal androgen receptor signalling.…”
Section: Discussionmentioning
confidence: 94%
“…However, standard androgen deprivation did not consistently suppress androgen-dependent gene expression. Many androgen-responsive genes were not suppressed even after 9 months of neoadjuvant androgen deprivation therapy [30]. Androgenindependent prostate cancer may be the consequence of molecular events that are mediated by abnormal androgen receptor signalling.…”
Section: Discussionmentioning
confidence: 94%
“…ADT with either surgical or medical castration usually results in a response rate of 70-80% with a 12-33 months duration of progression-free survival . However, after an average of 24 months, the tumors almost always recur and no longer respond to ADT (Eisenberger et al, 1998), even though the prostate tumors still express AR Mostaghel et al, 2007). Interestingly, cell sorting of these ADT-refractory tumors found that the prostatic epithelial basal cell marker, cytokeratin 5 (CK5) (Bruchovsky et al, 1990;van Leender et al, 2001) increased from 29 to 75%, an observation consistent with the expansion of basal intermediate-like tumor cells observed in transgenic adenocarcinoma mouse prostate (TRAMP) mice with selective knockout of AR (ARKO) in prostatic epithelium (pes-ARKO-TRAMP) and inducible ARKO-TRAMP (ind-ARKO-TRAMP) mice (see details in section 'AR dual functions in prostate cancer progression and metastasis').…”
Section: Adt In Prostate Cancer Patientsmentioning
confidence: 99%
“…However, there is invariably a return of tumour that is castration resistant. These tumours are commonly referred to as androgen-independent (AI), although castration-resistant may be a more appropriate term since they still contain significant levels of T and dihydrotestosterone (Mostaghel et al, 2007). In castration-resistant tumours, there is an increase in angiogenesis that is associated with an increase in MMP-9 (London et al, 2003).…”
Section: Androgensmentioning
confidence: 99%